PROBLEMS AND PROSPECTS OF RETIREMENT ADJUSTMENT ON FAMILIES OF RETIREES AMONG CIVIL SERVANTS IN EKITI STATE, NIGERIA - Olatunde, Ayodeji; Onyinye, Theresa (European Scientific Journal, ESJ, 2013)
Retirement is the act of retiring or the state of being retired, i.e. to withdraw oneself from business, public life or and to remove from active service. Data for this study were collected from primary and secondary sources. A total number of four hundred (400) questionnaires were administered in this research work, out of which three hundred and seventy eight (378) were returned. The questionnaires were administered using purposive and stratified random sampling techniques. Descriptive and frequency tables, using percentages were adopted in the analysis of the data collected. Results from the study revealed that delay in payment of pension; maladjustment and psychological adjustment were some of the problems of retired Civil Servants in the study area. This study therefore recommends that various establishments in Ekiti State should be encouraged to organize retirement counselling for their workers to enable them prepare for the obvious eventuality.